2017
DOI: 10.1007/s10826-017-0941-z
|View full text |Cite
|
Sign up to set email alerts
|

Foster children’s behavioral development and foster parent stress: testing a transactional model

Abstract: The goal of this three-wave longitudinal study was to analyze foster parent stress and foster children’s internalizing and externalizing behaviors in a transactional framework. Participants in this study were 237 children in foster care in the Netherlands with, mostly, long placement durations (M = 56.86 months, SD = 49.10 months). We examined concurrent, prospective unidirectional and bidirectional relations between foster children’s behavior and foster parent stress by using cross-lagged structural equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…Nonetheless, our study suggests that foster parent stress and foster children's mental health are correlated, which is in line with previous research (e.g., Kelley et al 2011;McSherry et al 2018;Murray et al 2011). However, only a few longitudinal studies have examined the directionality of the effects (Gabler et al 2018;Goemans et al 2018a;Lohaus et al 2018). These studies found significant weak to moderate correlations between stress of parents at the first time point and mental health of foster children at a later time point.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nonetheless, our study suggests that foster parent stress and foster children's mental health are correlated, which is in line with previous research (e.g., Kelley et al 2011;McSherry et al 2018;Murray et al 2011). However, only a few longitudinal studies have examined the directionality of the effects (Gabler et al 2018;Goemans et al 2018a;Lohaus et al 2018). These studies found significant weak to moderate correlations between stress of parents at the first time point and mental health of foster children at a later time point.…”
Section: Discussionsupporting
confidence: 91%
“…These studies found significant weak to moderate correlations between stress of parents at the first time point and mental health of foster children at a later time point. Two of these studies (Goemans et al 2018a;Lohaus et al 2018) tested this relation in a multivariate model using structural equation modeling, and found no significant prospective pathways from foster parent stress to foster children's behavior problems, meaning that foster parent stress did not predict foster children's mental health. As Lohaus et al (2018) suggested, identifying prospective pathways might be difficult if most variance of later assessments is already explained by the previous assessments, which is shown by the high stability across assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Foster and adoptive parents often experience challenges with and have concerns about their children's attachment security, behavior problems, and (previously or currently) experienced stress. They often experience elevated levels of stress, because the placement, the caregiving of, and the interacting with children who (due to their adverse experiences) show behavior problems can be stressful (Goemans, Van Geel, & Vedder, 2018). Such elevated stress levels can inhibit parents’ sensitive (disciplining) behavior while interacting with the child (Feldman, Weller, Zagoory-Sharon, & Levine, 2007).…”
Section: Intervention Programs For Foster and Adoptive Parentsmentioning
confidence: 99%
“…Evolving trends and behavioral patterns are often observed and made available as scientific findings. Some examples can be seen in [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] . Different statistical analysis can be useful for further behavioral analysis [27] , [28] , [29] , [30] , [31] , [32] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%